ABILITY TO READ THE QUR'AN THROUGH MEDIATION OF READING INTENSITY: THE INFLUENCE OF CLASSICAL READING AND LISTENING STRATEGIES AND SELF-INTELLIGENCE IN JUNIOR HIGH SCHOOL STUDENT - Anggarini, Wahyu Sandra; Wibowo, Arif; Daryono, Rihab Wit (Abjadia : International Journal of Education, 2024)
Reading intensity helps strengthen and maximize the positive effects of both factors, so that students can achieve better Qur'an reading skills. Without high reading intensity, the influence of classical strategies and self-intelligence may not be fully effective in improving students' Qur'an reading skills. This study aims to explore the role of reading intensity in mediating the influence of classical strategies and self-intelligence on Qur'an reading skills. The method used in this study was purposive sampling with random sampling method. The sample taken was 103 students at Madrasah Diniyah SMP PGRI Selur. The analysis in this study used PLS-SEM which aims to analyze data and test contextual models. From the results of the analysis, classical strategies do not have a significant effect on students' reading intensity and Qur'an reading skills. From the results of this study, it was found that the most determining factor in improving students' Qur'an reading skills is self-awareness of 88.90%. Based on these results, reading intensity does mediate the influence of self-intelligence on Qur'an reading skills and does not mediate classical strategies on Qur'an reading skills. This study provides an overview of how students' ability to read the Qur'an can be improved through their own intelligence and is also influenced by the level of reading intensity. Thus, this study can provide an in-depth overview of the influence of internal and external factors that can affect the level of success in improving each student's ability to read the Qur'an.